DETERMINING WEIGHTCRITERIA/SUB-CRITERIA IN SELECTING PUBLIC CONSTRUCTION WORK CONTRACTOR - Mardiaman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Determining weight criteria and sub-criteria in selecting public construction work contractorswas a crucial point for project success. Various countries have practice methods of choosing a construction work contractor in e-procurement. The lowest-price process causes problems. The combination of price evaluation and technical capability is considered preferable. However, the determination of the ability to weight the criteria and sub-criteria is still unclear. Determining each criterion and sub-criteria weight makes it easier for the government to select contractors with good performance. Besides, the contractor feels that the selection in the construction tender has not fair and transparent. The method of determining the total weight of the criteria and sub-criteria for deciding on the winner of a construction tender uses a hierarchical analysis of the suitable process. The distribution of questions containing the criteria and sub-criteria was carried out to 101 purposively: government officer (9), contractor (37), consultant (15), construction services association (24), state-owned construction company (16). Participants choose the level of importance based on pairwise comparisons of each criterion and sub-criteria using the Saaty scale. The period for collecting the Questioner was a month in January 2020.Distributed question sheets are written in a google.doc and distributed via email and WhatsApp.From the analysis of the answers that have been collected using the analytical hierarchic process (AHP), the results of the weight of financial performance criteria are obtained (0,436), technical performance (0,343), health and safety policy (0,115) dan past performance (0,106). Simultaneously, the highest sub-criteria was Stabilitas financial stability (0.374), the lowest unsuitable experienced(0,041). This result stressed the importanceofproper input criteria and sub-criteria to assess the awarded contractor to deliver the project in e-procurement. the implication for the study, the government shared the elected criteria and sub-criteria by doing socialization to a contractor that involved in bidding